Correlation of Liver Function Test with Different Age and Sex Group and with Ferritin Level in Thalassemia (Indian Journal of Public Health Research & Development, 2020)
Thalassemia is the most common genetic blood disease in the world and varies in different population groupin the world. In thalassemic patients liver damage is augmented when age of the patients are increase. Theseare due to increasing age with advancement of disease progression, repeated blood transfusion, less use/intolerance of iron chelating agent, decreased activity of hepatocyte to rescue them in such excess billirubinand iron flood. Secondary to hypersplenism.Iron overload due to frequent transfusions in ?-thalassemia results in abnormal organ function tests. Properand timely screening of these parameters can help in early diagnosis & prevention of iron overload. Ironoverload is a main leading cause of elevated liver enzymes, and presence of HCV infection is significantlyrelated to the increased iron overload14. Liver injury whether acute or chronic, eventually results in anincrease in serum concentrations of Alanine transaminase (ALT) and Aspartate transaminase (AST). Intransfusion dependent thalassemia patients iron overload is often inevitable and exposed to transfusionassociated infections. Apart from these when the age is more, the disease progresses with their complicationlike hepatic injury. The thalassemia patient develops liver fibrosis as a result of iron overload due to excessiveblood transfusion and also from excess intestinal absorption. N Sultana et al.6 showed that serum ferritin andserum bilirubin parameter of iron over load and jaundice are correlated.
Keywords: Thalassemia, liver function test, ferritin.